Community-Oriented Graduate Competency Development in Islamic Higher Education: The Role of Diploma Supplement and Industry Collaboration - Rusdiyah, Rusdiyah; Anshari, Mukhlis; Hafidzi, Anwar (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
This study explores the role of the Diploma Supplement (Surat Keterangan Pendamping Ijazah / SKPI) and academic–industry collaboration in strengthening graduate competencies in Islamic higher education from a community-based socio-religious perspective. Using a mixed-methods approach, the research involved 111 respondents consisting of study program managers, students and alumni, and industry partners at UIN Antasari Banjarmasin. Quantitative data were analyzed descriptively, while qualitative responses were examined thematically. The findings indicate that SKPI implementation and sustained collaboration with industry effectively enhance graduates’ professional readiness and practical skills. Beyond employability outcomes, the study reveals that competency documentation and institutional collaboration also strengthen graduates’ social legitimacy, ethical responsibility, and capacity to contribute to community development within Muslim society. The study concludes that Islamic higher education institutions play a strategic role in integrating professional competence, Islamic values, and community engagement to support sustainable socio-religious development.